MANAJEMEN INOVASI PELAYANAN SISTEM INFORMASI PUSKESMAS PAPERLESS (SIMPLE) DI PUSKESMAS TARIK KECAMATAN TARIK KABUPATEN SIDOARJO - Muhammad Afrizal Anam; Eva Hany Fanida (Publika, 2021)
The government seeks to improve the quality of public services through innovation by utilizing information and communication technology in all fields, including the health sector. Tarik Health Center which is a health facility that makes an innovation, namely the Health Center Information System Paperless (SIMPLE). SIMPLE is a software internal that is integrated in all health center services without paper passing. This innovation is motivated by the large number of patient visits and the amount of paper usage. In its implementation there are problems such as changing the mindset of employees from writing to typing, and the technical system. The purpose of this research is to describe innovation and to know the implementation of SIMPLE Tarik Health Center. The type of research is descriptive qualitative research. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The focus of the research uses innovation management theory from Utomo (2017) with five indicators, namely: idea exploration, innovation incubation, innovation dissemination/diffusion, innovation adoption/replication/modification, and innovation actualization. The results of the study show SIMPLE based on Utomo (2017), namely: First, Tarik Health Center creates innovations based on service problems, improving employee performance, and responding to challenges from BPJS (Social Security Administrative Bodies). Second, the Tarik Health Center prepares the infrastructure needs for internet networks, computers, and changes the mindset of employees working with a computerized system. Third, the Tarik Health Center conducts socialization to partners through SIAP TARIK (patient queuing application) which is part of the SIMPLE program. Fourth, SIMPLE will be replicated to all health centers in Sidoarjo Regency, but it is still constrained by Covid-19. Fifth, the Tarik Health Center carries out monitoring and evaluation activities that are carried out every week such as upgrading the system paperless for the service needs of the Tarik Health Center Keywords : Service innovation, Health services, SIMPLE Pemerintah berupaya meningkatkan kualitas pelayanan publik melalui inovasi dengan memanfaatkan teknologi informasi dan komunikasi dalam segala bidang, termasuk bidang kesehatan. Puskesmas Tarik yang merupakan fasilitas kesehatan yang membuat suatu inovasi yaitu Sistem Informasi Puskesmas Paperless (SIMPLE). SIMPLE merupakan software internal yang terintegrasi pada keseluruhan pelayanan puskesmas tanpa kertas lewat. Inovasi ini dilatarbelakangi banyaknya jumlah kunjungan pasien dan jumlah penggunaan kertas. Dalam implementasinya terdapat masalah seperti mengubah mindset pegawai dari menulis menjadi mengetik, dan sistem secara teknis. Tujuan penelitian untuk mendeskripsikan inovasi dan mengetahui penerapan dari SIMPLE Puskesmas Tarik. Jenis penelitian yakni penelitian deskriptif kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Teknik analisis data yakni pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Fokus penelitian menggunakan teori manajemen inovasi dari Utomo (2017) dengan lima indikator yakni: eksplorasi ide, inkubasi inovasi, diseminasi/difusi inovasi, adposi/replikasi/modifikasi inovasi, dan aktualisasi inovasi. Hasil penelitian menunjukkan SIMPLE berdasarkan Utomo (2017), yaitu: Pertama, Puskesmas Tarik menciptakan inovasi berdasarkan permasalahan pelayanan, peningkatan kinerja pegawai, dan menjawab tantangan dari BPJS (Badan Penyelenggara Jaminan Sosial). Kedua, Puskesmas Tarik menyiapkan kebutuhan infrastruktur jaringan internet, komputer, dan mengubah mindset pegawai bekerja dengan sistem komputerisasi. Ketiga, Puskesmas Tarik melakukan sosialisasi kepada para mitra melalui SIAP TARIK (aplikasi antrian pasien) yang merupakan bagian dari program SIMPLE. Keempat, SIMPLE akan di replikasi ke seluruh puskesmas di Kabupaten Sidoarjo, namun masih terkendala Covid-19. Kelima, Puskesmas Tarik melakukan kegiatan monitoring dan evaluasi yang dilakukan setiap minggu seperti upgrading sistem paperless untuk kebutuhan pelayanan puskesmas Tarik. Kata Kunci : Inovasi pelayanan, Pelayanan Kesehatan, SIMPLE